Aktivitas Fisik Lansia Penderita Diabetes Mellitus Tipe 2 Di Wilayah Kerja Puskesmas Lubuk Buaya Tahun 2021 - Nadia Purnama Dewi; Dessy Abdullah; Adeteti Vani; Khomeini Khomeini (Stikes Syedza Saintika Padang, 2021)
Type 2 diabetes mellitus is a chronic disease, characterized by increased blood glucose levels from normal values. Type 2 diabetes mellitus has many risk factors, including less physical activity. This devotion is in the form of counseling to the elderly on how to do safe and good physical activity done in old age to maintain blood glucose stability. Counseling is carried out at the Puskesmas Lubuk Buaya district of Koto Tangah as a partner that facilitates this community service. The purpose of community service is to counsel the elderly about good physical activity done in old age and increase the elderly's knowledge of physical activity plays a role in maintaining the stability of blood glucose levels. The purpose of community service is to counsel the elderly about good physical activity done in old age and increase the elderly's knowledge of physical activity plays a role in maintaining the stability of blood glucose levels. Counseling activities were carried out on Saturday, June 26, 2021 at 11.00 WIB to finish at Puskesmas Lubuk Buaya. The participants are elderly who are in the working area of Puskesmas Lubuk Buaya. Furthermore, discussion and question and answer sessions and the conclusion that community service is one of the activities part of Tri Darma Higher Education in the form of counseling activities to the community conducted by lecturers.